2021
DOI: 10.1007/s10900-021-01006-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in COVID-19 School Related Inquiries Using 311 New York City Open Data

Abstract: This study aimed to assess the coronavirus disease (COVID-19) school-related information New York City residents sought through the 311 Call Center. July to November inquiries were downloaded from the NYC Open Data website for 2018-2020. Calls were categorized as related to "Schools", "Access", "Food", "Hospitals", "Transportation", and "Unemployment". Overall call types, and among school-related calls, detailed call types, were compared over the years, using chi-squared tests. School-related inquiries increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Compared to existing literature, the share of covid-related requests that we found for Kansas City of 4.3% is similar to the share of covid-specific calls in New York City (4.14%) and the share of pandemic-specific requests in Orange County Florida (5.15%) [20,23] . Like Pamukcu et al, 311 data in Kansas City also showed declines in requests in comparable categories to street conditions and traffic signal conditions [22] .…”
Section: Relation To Existing Literaturesupporting
confidence: 76%
See 2 more Smart Citations
“…Compared to existing literature, the share of covid-related requests that we found for Kansas City of 4.3% is similar to the share of covid-specific calls in New York City (4.14%) and the share of pandemic-specific requests in Orange County Florida (5.15%) [20,23] . Like Pamukcu et al, 311 data in Kansas City also showed declines in requests in comparable categories to street conditions and traffic signal conditions [22] .…”
Section: Relation To Existing Literaturesupporting
confidence: 76%
“…If successful, it can be used as a framework to improve resilience and crisis response strategies. There are a few studies on the patterns of 311 systems during COVID-19, focusing mainly on New York City, Dallas, and Orange County [20,21] . In New York City, the 311 systems added specific categories and descriptors for calls related to the pandemic, which greatly helped capture the reaction of its citizen to the crisis and associated responses taken by the municipality agencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social governance has been considered a two-way management model in the big data era (Bernhard et al ., 2018). A government hotline is one way to run social governance Such public service facilities around the globe are 311 citizen service systems in the USA (Agonafir et al , 2022; Feng and Jiao, 2021; Rosés et al , 2021; Biresselioglu et al , 2022; Cao et al , 2014; Eugene et al ., 2021), the Preston DWP call center system in the United Kingdom, the New Delhi “Kisan” call center in India (Wang, 2015) and China's 12,345 government hotline. While governments collect information on several subjects related to public opinions in the text form of appeals, complaints and suggestions, there appear several issues such as dispatching work orders, classification, standardization, crunching and so on.…”
Section: Introductionmentioning
confidence: 99%